A note on the conditional residual lifetime of a coherent system under double monitoring. Issue 10 (19th May 2018) - Parvardeh, A.; Balakrishnan, N.; Arshadipour, Azam
ABSTRACT: In this note, we derive some mixture representations for the reliability function of the conditional residual lifetime of a coherent system with n independent and identically distributed (i.i.d.) components under the condition that at time t 1 the j th failures has occurred and at time t 2 the k th failures ( j < k ) have not occurred yet. Based on the mixture representations, we then discuss the stochastic comparisons of the conditional residual lifetimes of two coherent systems with i.i.d. components.